Tin-based photoresist compositions and methods for making same
Patent Information
- Application Number
- JP2022551802
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-02-27
- Filing Date
- 2021-02-25
- Publication Date
- 2025-03-03
- Estimated Expiration
- 2041-02-25
Smart Images

Figure 0007638007000002 
Figure 0007638007000003 
Figure 0007638007000004
Abstract
Description
[Technical field]
[0001] This application claims the benefit of the earlier filing date of U.S. Provisional Application No. 62 / 982,599, filed February 27, 2020, the entirety of which is incorporated herein by reference. (Statement on Government Support)
[0002] This invention was made with United States Government support under CHE-1606982 awarded by the National Science Foundation. The United States Government has certain rights in this invention. (Technical field)
[0003] The present disclosure relates to tin-based photoresist compositions and methods of making and patterning the compositions. Summary of the Invention
[0004] The present disclosure relates to tin-based photoresist compositions and methods of making and patterning the compositions. In one embodiment, the tin-based composition comprises R q S n O m (OH) x (HCO 3 ) y (CO 3 ) z where R comprises: (i) C 1 ~C 10 or (ii) a heteroaliphatic, heteroaryl, or heteroaryl-aliphatic having 1-10 carbon atoms and one or more heteroatoms, where q=0.1-1, x≦4, y≦4, z≦2, m=2-q / 2-x / 2-y / 2-z, and (q / 2+x / 2+y / 2+z)≦2. q S n O m (OH) x (HCO 3 ) y (CO 3 ) z where R comprises: (i) C 1 ~C10 (i) a hydrocarbyl or (ii) a heteroaliphatic, heteroaryl or heteroaryl - aliphatic containing 1 to 10 carbon atoms and one or more heteroatoms, where q = 0.1 to 1, x ≤ 3.9, y ≤ 3.9, z ≤ 1.95, m = 2 - q / 2 - x / 2 - y / 2 - z and (q / 2 + x / 2 + y / 2 + z) ≤ 2. In certain embodiments, R is C 1 ~C 5 such as alkyl, is C 1 ~C 10 aliphatic. In some examples, R is n - butyl. In any of the foregoing or following embodiments, x, y and z can have values of (i) 0 < x ≤ 3, (ii) 0 < y ≤ 3 or (iii) 0 < z ≤ 1.5, or (iv) any combination of (i), (ii) and (iii).
[0005] The component can include a substrate and a film on at least a part of the substrate, and the film comprises a tin - based composition disclosed herein. The film can be patterned on the substrate. In some embodiments, (i) the film has an average thickness in the range of 2 to 1000 nm, or (ii) the film has a root - mean - square surface roughness of less than 1.5 nm, or (iii) both (i) and (ii).
[0006] In some embodiments, a method for manufacturing a tin - based photoresist composition comprises exposing RSnX 3 to the atmosphere, thereby generating [RSnOH(H 2 O)X 2 2 , where X is a halogen, R is defined as above, preparing a solution comprising [RSnOH(H 2 O)X 2 2 and a solvent, depositing the solution on the substrate, heating the deposited solution and the substrate to generate a film comprising [(RSn) 12 O 14 (OH) 6 X 2 on the substrate, and [(RSn) 12 O 14 (OH) 6 ]X 2 The film having the formula (I) is contacted with an aqueous ammonia solution to form a film having the formula (I) on the substrate. 12 O 14 (OH) 6 ]X 2 and forming a film comprising: [(RSn) 12 O 14 (OH) 6 ]X 2 Heating the deposition solution and the substrate to produce a film on the substrate comprising may include heating at a temperature in the range of 60-100° C. for 1-5 minutes.
[0007] In any of the above or below embodiments, R is C 1 ~C 5 Alkyl, etc., C 1 ~C 10 In some implementations, R is n-butyl. In any of the above or below embodiments, the deposition solution and the substrate are heated to deposit [(RSn) 12 O 14 (OH) 6 ]X 2 Producing a film comprising the above may include heating at a temperature in the range of 60-100° C. for 1-5 minutes.
[0008] In any of the above or below described embodiments, the method comprises the steps of: 12 O 14 (OH) 6 ](OH) 2 and irradiating at least a portion of the film with an electron beam or light having a wavelength in the range of 10 nm to less than 400 nm to produce an irradiated film. In some embodiments, the irradiation is performed by irradiating with light having a wavelength in the range of 10 to 260 nm or by irradiating with light having a wavelength of 125 μC / cm 2 In some embodiments, the irradiation includes irradiating the substrate with an electron beam at a dose of 125 to 1000 μC / cm 2 In any of the above embodiments, the irradiation includes irradiating the electron beam with a dose of [(RSn) 12 O 14 (OH) 6 ](OH)2 The irradiated portion of the film can break 10 to 100% of the R-Sn bonds.
[0009] In any of the embodiments described above or below, the method may further include a post-irradiation treatment. In some embodiments, the method further includes (i) exposing the irradiated film to air at ambient temperature for at least 3 hours, or (ii) heating the irradiated film in air at a temperature in the range of 100-200° C. for 2-5 minutes, whereby the irradiated portions of the irradiated film are converted to CO 2 in the air. 2 Adsorbs R q S n O m (OH) x (HCO 3 ) y (CO 3 ) z where q=0.1-1, x≦4, y≦4, z≦2, m=2-q / 2-x / 2-y / 2-z, and (q / 2+x / 2+y / 2+z)≦2. In one embodiment, q=0.1-1, x≦3.9, y≦3.9, z≦1.95, m=2-q / 2-x / 2-y / 2-z, and (q / 2+x / 2+y / 2+z)≦2.
[0010] In some embodiments, [(RSn) 12 O 14 (OH) 6 ](OH) 2 A portion of the film comprising the film is irradiated to form a patterned film, and the method comprises: irradiating the patterned film with a 12 O 14 (OH) 6 ](OH) 2 wherein the irradiated portion of the film is contacted with a solvent in which [(RSn) 12 O 14 (OH) 6 ](OH) 2 The irradiated portions of the patterned film are rendered less soluble for a time effective to dissolve the irradiated portions of the patterned film.
[0011] Also encompassed by the present disclosure is a component comprising a substrate and a film on at least a portion of the substrate, the film being made by the method disclosed herein. In one embodiment, the film is a [(RSn) 12 O 14 (OH) 6 ](OH) 2 In some embodiments, (i) the film has a root mean square surface roughness of 0.8 nm or less, such as 0.5 nm or less, or (ii) the film has undetectable levels of Cl as detected by X-ray photoelectron spectroscopy. - or (iii) both (i) and (ii). In an independent embodiment, the membrane has R q S n O m (OH) x (HCO 3 ) y (CO 3 ) z where q=0.1-1, x≦4, y≦4, z≦2, m=2-q / 2-x / 2-y / 2-z, and (q / 2+x / 2+y / 2+z)≦2. In another independent embodiment, the membrane comprises R q S n O m (OH) x (HCO 3 ) y (CO 3 ) z where q=0.1 to 1, x≦3.9, y≦3.9, z≦1.95, m=2−q / 2−x / 2−y / 2−z and (q / 2+x / 2+y / 2+z)≦2.
[0012] The foregoing and other objects, features and advantages of the present invention will become more apparent from the following detailed description which proceeds with reference to the accompanying drawings. [Brief description of the drawings]
[0013] [Figure 1] Ball and stick representation of (C4H9Sn)2(OH)2Cl4(H2O)2(Sn2); 1H and 119Sn NMR spectra show that the structure retains 2-heptanone. [Figure 2A]This is the ball and stick representation of [(n-C4H9Sn)12O14(OH)6](OH)2(Sn12OH). [Figure 2B] Small angle X-ray scattering data showing that Sn2 was converted to Sn12OH. [Diagram 3] FIG. 13 shows XPS spectra of Sn2 film before and after base immersion. [Figure 4A] 1A-1C are atomic force microscope (AFM) images showing that deposition of Sn12 from the Sn2 precursor produces a much smoother film than direct deposition from the Sn12 precursor. [Figure 4B] 1A-1C are atomic force microscope (AFM) images showing that deposition of Sn12 from the Sn2 precursor produces a much smoother film than direct deposition from the Sn12 precursor. [Figure 5A] FIG. 1 shows a temperature programmed desorption / mass spectrometry (TPD-MS) spectrum of an Sn2 film. [Figure 5B] FIG. 1 shows a temperature programmed desorption / mass spectrometry (TPD-MS) spectrum of a Sn12OH film. [Figure 6] FIG. 4C shows ESI-MS electrospray ionization mass spectrometry spectra of the membranes of FIGS. 4A and 4B. [Figure 7] FIG. 13 shows the surface roughness of Sn2 films baked at selected temperatures after base immersion. [Figure 8] FIG. 13 shows the TPD-MS spectrum of the Sn2 film immediately after post-apply bake and NH3(aq) treatment. [Figure 9A] Figure 13 is a TPD-MS spectrum tracking the desorption of H2O (8A) at low temperature versus time for the film. [Figure 9B] 13 is a TPD-MS spectrum tracking the desorption of CO2 (8B) versus time for the membrane. [Figure 10A] This is a TPD-MS spectrum showing that the desorption peak of H2O (9A) at low temperature is mostly removed by baking at 140°C for 3 minutes. [Figure 10B] This is a TPD-MS spectrum showing that the desorption peak of CO2 (9B) is largely removed by baking at 140°C for 3 minutes. [Figure 11] 1 is a TPD-MS spectrum showing the main fragments of 1-butene. [Figure 12] 1 is a TPD-MS spectrum showing the main fragments of butane. [Figure 13] FIG. 1 is an illustration of the decomposition of an n-butyl ligand and subsequent electron impact ionization of the decomposition products. [Figure 14] Figure 2 shows the TPD-MS spectral signals associated with n-butyl desorption from samples exposed to 0, 300 and 1000 μC / cm2. [Figure 15] 13 is a graph showing loss curves for TPD-MS spectral signals associated with n-butyl desorption from samples exposed to 0, 300 and 1000 μC / cm2. [Figure 16] 1 is a graph showing film thickness as a function of irradiation dose. [Figure 17] Scanning electron microscope image of 25 nm lines written on a 100 nm pitch using an electron beam dose of 500 μC / cm2. [Figure 18] Reverse contrast cross-sectional cryo-STEM image of an exposed and undeveloped sample. [Figure 19] Cryo-EELS spectrum at 10 nm resolution of the sample in FIG. 17. [Figure 20] 1 is a graph showing film thickness as a function of irradiation dose for arrays aged 0.25, 3, 24 and 144 hours. [Figure 21] Images of dose arrays in vacuum (left) and air (right) after a 2 hour delay and then developed in acetone for 30 seconds. [Figure 22A] TPD-MS spectra of unexposed and 1000 μC / cm2 exposed samples tracking the desorption of n-butyl in air with no delay time. [Figure 22B] TPD-MS spectra of unexposed and 1000 μC / cm2 exposed samples tracking water desorption in air with no delay time. [Figure 22C]TPD-MS spectra of unexposed and 1000 μC / cm2 exposed samples tracking carbon dioxide desorption in air with no delay time. [Figure 23A] Figure 13 shows the TPD-MS spectra of n-butyl desorbed from a film exposed to 1000 μC / cm2 in air before and after a 10 day delay. [Figure 23B] Figure 13 is a TPD-MS spectrum of H2O desorbed from a film exposed to 1000 μC / cm2 in air before and after a 10 day delay. [Figure 23C] Figure 13 is a TPD-MS spectrum of CO2 (23C) desorbed from a film exposed to 1000 μC / cm2 in air before and after a 10 day delay. [Figure 24] Figure 13 is a TPD-MS spectrum of the butyl fragment after exposure to 1000 μC / cm2 after a 10 day delay in air. [Figure 25A] Figure 13 is a TPD-MS spectrum of n-butyl desorbed from a film exposed to 300 μC / cm2 after a 1 day delay in air. [Figure 25B] Figure 13 is a TPD-MS spectrum of water desorbed from a film exposed to 300 μC / cm2 after a 1 day delay in air. [Figure 25C] Figure 13 is a TPD-MS spectrum of carbon dioxide desorbed from a film exposed to 300 μC / cm2 after a 1 day delay in air. [Figure 26A] Figure 13 is a TPD-MS spectrum of n-butyl desorbed from a film exposed to 500 μC / cm2 after a 6 day delay in air. [Figure 26B] Figure 13 is a TPD-MS spectrum of water desorbed from a film exposed to 500 μC / cm2 after a 6 day delay in air. [Figure 26C] Figure 13 is a TPD-MS spectrum of carbon dioxide desorbed from a film exposed to 500 μC / cm2 after a 6 day delay in air. [Figure 27A] FIG. 13 shows that the n-butyl groups can be removed by heating the Sn12 film in air. [Figure 27B] FIG. 1 shows that n-butyl-depleted membranes absorb HO. [Figure 27C] FIG. 1 shows that n-butyl-depleted membranes absorb CO2. [Figure 28] TPD-MS spectra of m / z=41 (n-butyl) for unexposed film, film exposed to UV light for 10 minutes, and film exposed to UV light for 10 minutes with a delay in air for 6 days. [Figure 29] TPD-MS spectra of m / z=18 (H2O) of a film exposed to UV light for 10 min and a film exposed to UV light for 10 min and delayed in air for 6 days. [Diagram 30] TPD-MS spectra of m / z=44 (CO2) for a film exposed to UV light for 10 min and a film exposed to UV light for 10 min and delayed in air for 6 days. [Diagram 31] FIG. 2 is a TPD-MS spectrum of a film exposed to UV light for 10 min and delayed in air for 6 days, showing CO2 fragmentation and undetected butyl signals. [Diagram 32] FIG. 1 illustrates the chemical reactions to induce dissolution changes between exposed and unexposed areas of a Sn12OH film. [Diagram 33] 1 is a graph showing that both H2O and CO2 are required to achieve dissolution contrast in an e-beam exposed Sn12 film. [Figure 34A] Figure 13: TPD-MS spectra of n-butyl desorption from the film after irradiation at 1000 μC / cm2 and after post-exposure bake (PEB) at 140°C and 180°C for 3 min. [Figure 34B] Figure 13 TPD-MS spectra of water desorption from the film after irradiation at 1000 μC / cm2 and after post-exposure bake (PEB) at 140°C and 180°C for 3 min. [Diagram 35] FIG. 13 shows thickness measurements of dose arrays exposed to no PEB, 100° C. PEB, 140° C. PEB and 180° C. PEB for 3 minutes. [Diagram 36]13 is a TPD-MS spectrum showing that heating induces the desorption of n-butyl groups from Sn12 films at low temperatures. [Figure 37] TPD-MS spectra showing CO2 desorption from the three dose arrays of Figure 32 after exposure to 1000 μC / cm2 and 3 min PEB at 140°C and 180°C. [Figure 38A] 13 is a TPD-MS spectrum showing the desorption of n-butyl following 3 min PEB at 320° C. either immediately or after a 6 day delay. [Figure 38B] 13 is a TPD-MS spectrum showing desorption of CO2 following 3 min PEB at 320° C. either immediately or after a 6 day delay. [Figure 39] 1 is a table of TPD-MS spectra of unexposed and unbaked exposed samples, or samples baked at 140° C. or 180° C. [Figure 40A] 13 is a TPD-MS spectrum of an unexposed sample showing hydrolyzed Sn as the CO2 reaction site. [Figure 40B] 13 is a TPD-MS spectrum of an exposed sample after PEB showing hydrolyzed Sn as CO2 reaction sites. [Figure 41A] 13 is a TPD-MS spectrum of n-butyl elimination after PEB at 180° C. [Figure 41B] 13 is a TPD-MS spectrum of water desorption after PEB at 180° C. [Figure 41C] 13 is a TPD-MS spectrum of carbon dioxide desorption after PEB at 180° C. [Figure 42A] This is a TPD-MS spectrum after TGA of Sn12OH(42A) in N2. [Figure 42B] This is a TPD-MS spectrum after TGA of Sn12OH(42B) baked in air. [Diagram 43] SEM image of 10 nm (horizontal) and 14 nm (vertical) lines on 60 nm pitch produced by Sn2 deposition, conversion to Sn12OH, e-beam exposure, post-exposure bake at 140 °C, and development in 2-heptanone. [Diagram 44] SEM images of line-and-space and dot patterns produced by Sn2 deposition, conversion to Sn12OH by NH3(aq) immersion, e-beam exposure, post-exposure bake at 180 °C, and development in 2-heptanone. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] Embodiments of tin-based photoresist compositions are disclosed, as well as methods of making and patterning the compositions.
[0015] I. Definitions and Abbreviations The following explanations of terms and abbreviations are provided to better describe the present disclosure and guide those skilled in the art in the practice of the present disclosure. As used herein, "comprises" means "including," and the singular forms "a" or "an" or "the" include plural references unless the context clearly dictates otherwise. The term "or" refers to a single element of the listed alternative elements or a combination of two or more elements, unless the context clearly dictates otherwise.
[0016] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which this disclosure belongs.In carrying out or testing this disclosure, methods and materials similar or equivalent to those described herein may be used, and suitable methods and materials are described below.The materials, methods, and examples are merely illustrative and are not intended to be limiting.Other features of this disclosure will be apparent from the following detailed description and claims.
[0017] Disclosure of numerical ranges should be understood as referring to each discrete point within the range, including the endpoints, unless otherwise indicated. Unless otherwise indicated, all numbers expressing amounts of ingredients, molecular weights, percentages, temperatures, times, and the like, used in the specification or claims should be understood to be modified by the term "about". Thus, unless otherwise implicitly or explicitly indicated, or unless the context is properly understood by those skilled in the art to have a more determinative structure, the numerical parameters indicated are approximations that may depend on the desired properties sought and / or the detection limits under standard testing conditions / methods known to those skilled in the art. When directly and explicitly distinguishing the embodiments from the prior art discussed, the numerical values of the embodiments are not approximations unless the word "about" is recited.
[0018] Although there are alternatives for the various components, parameters, operating conditions, etc. described herein, it is not meant that the alternatives are necessarily equivalent and / or perform equally well. Nor is it meant that the alternatives are listed in order of preference, unless otherwise stated. Definitions of common terms in chemistry can be found in Richard J. Lewis, Sr. (ed.), Hawley's Condensed Chemical Dictionary, 2016 (ISBN 978-1-118-13515-0), published by John Wiley & Ons, Inc. The presently disclosed compounds also include all isotopes of atoms present in the compounds, which may include, but are not limited to, deuterium, tritium, 14C, etc.
[0019] In order to facilitate review of the various embodiments of the disclosure, the following explanations of specific terms are provided:
[0020] Adsorption: The physical attachment or binding of ions and molecules to the surface of another molecule. Depending on the nature and strength of the bond between the adsorbate and the surface, adsorption may be characterized as chemisorption or physisorption.
[0021] Aliphatic: Substantially hydrocarbon-based compounds, or radicals thereof (e.g., C for the hexane radical), including alkanes, alkenes, and alkynes, including their cyclic equivalents, as well as linear and branched arrangements, and all configurational and structural isomers. 6 H 13 ).
[0022] Alkyl: A hydrocarbon group having a saturated carbon chain. The chain can be cyclic, branched or unbranched. Non-limiting examples of alkyl groups include methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl and decyl. The terms alkenyl and alkynyl refer to hydrocarbon groups having carbon chains containing one or more double or triple bonds, respectively.
[0023] Aromatic or aryl: An unsaturated cyclic hydrocarbon with alternating single and double bonds. Benzene is a six-carbon ring containing three double bonds and is a typical aromatic compound. If the aromatic ring portion contains a heteroatom, the group is a heteroaryl, not an aryl. Aryl groups can be monocyclic, bicyclic, tricyclic, or tetracyclic.
[0024] Arylaliphatic: a group containing an aromatic portion and an aliphatic portion, the point of attachment to the remainder of the molecule being through the aliphatic portion.
[0025] Coating: A layer of material on the surface of a substrate. Synonymous with the word "film."
[0026] Film: A layer of material on the surface of a substrate. Synonymous with "coating."
[0027] Halogen and Halide: As used herein, the terms “halogen (halo)” and “halide” refer to Cl, Br, or I.
[0028] Heteroaliphatic: an aliphatic compound or group having at least one carbon atom and at least one heteroatom in the chain, i.e., one or more carbon atoms are replaced with an atom having at least one lone pair of electrons (usually nitrogen, oxygen, phosphorus, silicon, or sulfur). Heteroaliphatic compounds or groups can be substituted or unsubstituted, branched or unbranched, cyclic or acyclic, and can include "heterocycle", "heterocyclyl", "heteroalicyclic", or "heterocyclic" groups.
[0029] Heteroaryl: An aliphatic compound or group having at least one heteroatom, i.e., one or more carbon atoms in the ring is replaced by an atom having at least one lone pair of electrons (usually nitrogen, oxygen, phosphorus, silicon, or sulfur).
[0030] Heteroarylaliphatic: A group with an aromatic portion and an aliphatic portion, where the point of attachment to the rest of the molecule is through the aliphatic portion and the group contains at least one heteroatom. Unless otherwise specified, the heteroatom can be in the aromatic or aliphatic portion.
[0031] Hydrocarbyl: A monovalent radical derived from a hydrocarbon. The hydrocarbyl radical may be linear, branched or cyclic and may be aliphatic, aryl or arylaliphatic.
[0032] Soluble: Capable of being molecularly or ionically dispersed in a solvent to form a homogeneous solution.
[0033] Solution: a homogeneous mixture of two or more substances. The solute (minor component) dissolves in the solvent (major component).
[0034] Sn 2 :(C 4 H 9 Sn) 2 (OH) 2 C l4 (H 2 O) 2
[0035] Sn12 OH (or Sn 12 ):(nC 4 H 9 Sn) 12 O 14 (OH) 8
[0036] II. Photoresist Compositions The present disclosure relates to embodiments of photoresist compositions and methods of making the photoresist compositions. In one embodiment, the photoresist composition comprises R q S n O m (OH) x (HCO 3 ) y (CO 3 ) z where R comprises: (i) C 1 ~C 10 or (ii) a heteroaliphatic, heteroaryl, or heteroaryl-aliphatic group containing 1-10 carbon atoms and one or more heteroatoms, where q=0.1-1, x≦4, y≦4, z≦2, m=2-q / 2-x / 2-y / 2-z, and (q / 2+x / 2+y / 2+z)≦2. q S n O m (OH) x (HCO 3 ) y (CO 3 ) z where R comprises: (i) C 1 ~C 10 or (ii) a heteroaliphatic, heteroaryl, or heteroaryl-aliphatic containing 1 to 10 carbon atoms and one or more heteroatoms, where q=0.1-1, x≦3.9, y≦3.9, z≦1.95, m=2-q / 2-x / 2-y / 2-z, and (q / 2+x / 2+y / 2+z)≦2.
[0037] In some embodiments, R is C 1 ~C 10Aliphatic, aryl or aryl - aliphatic, and the aliphatic moiety is the point of attachment to the Sn atom. In certain embodiments, R is C 1 ~C 5 such as aliphatic, C 1 ~C 10 is aliphatic. The aliphatic chain can be linear, branched or cyclic. In some examples, R is C 1 ~C 5 is alkyl. Examples of R groups include, but are not limited to, methyl, ethyl, n - propyl, isopropyl, n - butyl, iso - butyl (2 - methylpropyl), sec - butyl (butan - 2 - yl), tert - butyl, n - pentyl, 1,1 - methylpropyl, 2,2 - dimethylpropyl, 1,2 - dimethylpropyl, 1 - methylbutyl, 2 - methylbutyl, 3 - methylbutyl and 1 - ethylpropyl. In some embodiments, R is heteroaliphatic, heteroaryl or heteroaryl - aliphatic (where the heteroatoms can be in the aryl and / or aliphatic moieties and the aliphatic moiety is the point of attachment to the Sn atom), containing 1 to 10 carbon atoms and one or more heteroatoms. Suitable heteroatoms can include N, O, S and combinations thereof. The heteroaliphatic chain can be linear, branched or cyclic. In a particular example, R is n - butyl.
[0038] In any of the foregoing or following embodiments, q = 0.1 to 1. In some embodiments, q = 0.3 to 1 or 0.5 to 1. In any of the foregoing or following embodiments, x ≤ 4. In one embodiment, x ≤ 3.9. In some embodiments, 0 < x ≤ 4, 0 < x ≤ 3.9 or 0 < x ≤ 3. In any of the foregoing or following embodiments, y ≤ 4. In one embodiment, y ≤ 3.9. In some embodiments, 0 < y ≤ 4, 0 < y ≤ 3.9 or 0 < y ≤ 3. In any of the foregoing or following embodiments, z ≤ 2. In one embodiment, z ≤ 1.95. In some embodiments, 0 < z ≤ 2, 0 < z ≤ 1.95 or 0 < z ≤ 1.5.
[0039] In any of the embodiments described above or below, the photoresist composition may be deposited on a substrate as a film or layer. In some embodiments, the film has an average thickness in the range of 2 nm to 1000 nm and / or a root mean square (RMS) surface roughness of 1.5 nm or less. In certain embodiments, the average thickness is in the range of 2 to 750 nm, such as 2 to 500 nm, 2 to 250 nm, 5 to 250 nm, 10 to 100 nm, or 10 to 50 nm. The RMS surface roughness may be 1.5 nm or less, less than 1.5 nm, 1.2 nm or less, less than 1.2 nm, 1 nm or less, or less than 1 nm, such as in the range of 0.2 to 1.5 nm, 0.3 to 1.5 nm, 0.3 to 1.2 nm, 0.3 to 1 nm, or 0.3 to 0.75 nm.
[0040] III. METHODS OF MAKING AND PATTERNING PHOTORESIST COMPOSITIONS A smooth and dense film comprising the photoresist composition is desirable. In some embodiments, superior films are prepared by forming an OH-stabilized butyltin dodecamer in situ on a substrate, followed by forming a photoresist composition as disclosed herein.
[0041] R z SnO(2-(x / 2)-(x / 2)(OH) xOrganotin coatings having the general composition, where 0<(x+z)<4, have been shown to function well as radiation patternable materials, commonly known as photoresists. The use of organotin materials as photoresists sensitive to electron beam, ultraviolet (UV) radiation, and extreme ultraviolet (EUV) radiation is described in U.S. Pat. No. 9,310,684 to Meyers, entitled "Organometallic Solution Based High Resolution Patterning Compositions," and U.S. Pat. No. 10,228,618 to Meyers, entitled "Organotin Oxide Hydroxide Patterning Compositions, Precursors, and Patterning," both of which are incorporated herein by reference.
[0042] The present disclosure relates to a compound of the formula [RSnOH(H 2 O)X 2 ] 2 This paper describes the preparation of an organotin precursor represented by RSnX 3 With water, where X is a halide and R is as defined above. In one embodiment, RSnX 3 is exposed to the ambient air, thereby 2 O)X 2 ] 2 is generated. [RSnOH(H 2 O)X 2 ] 2 is RSnX 3 is formed spontaneously when exposed to the atmosphere for an effective period of time, e.g., 2 to 4 days. In some embodiments, X is Cl - In a particular example, R is n-butyl.
[0043] Generally, organotin oxide hydroxide coatings can be prepared by reacting hydrolysis-sensitive organotin precursor compositions with water. The aforementioned references describe organotin oxide hydroxide coatings prepared by spin-coating and deposition techniques. Patternable organotin oxide hydroxide coatings are prepared by reacting one or more RnSnL 4-n (n=1,2) can be formed by dissolving the hydrolysate of the composition in a suitable solvent and subsequently depositing it via spin coating. 4-n Due to the relatively high vapor pressure of the compositions, organotin oxide hydroxide coatings may also be prepared by vapor deposition techniques in which hydrolyzable gas-phase precursors are introduced from the ambient atmosphere into a sealed reactor and hydrolyzed as part of the vapor deposition process. 4-n The composition is 2 O, H 2 O 2 , O 3 , O 2 , C.H. 3 OH to form an organotin oxide hydroxide composition on a desired substrate. Vapor deposition techniques include ALD (atomic layer deposition), PVD (physical vapor deposition), CVD (chemical vapor deposition), and the like.
[0044] If solution deposition of an organotin coating is desired, [RSnOH(H 2 O)X 2 ] 2 In general, a solution comprising [RSnOH(H 2 O)X 2 ] 2 Any solvent in which the composition dissolves may be used. The choice of solvent may be further influenced by other parameters, such as its toxicity, flammability, volatility, viscosity, and potential chemical interactions with other materials. Suitable solvents include, for example, alcohols such as 4-methyl-2-pentanol, propylene glycol methyl ether (PGME), ketones such as 2-heptanone, esters such as propylene glycol monomethyl ether acetate (PGMEA), and / or mixtures thereof.
[0045] The concentration of the species in the solution may be evaluated on a Sn molar basis and may generally be selected for the desired physical properties of the solution and the desired coating. For example, a more concentrated solution will generally result in a thicker film and a less concentrated solution will generally result in a thinner film. In some applications, such as ultra-high resolution patterning, a thinner film may be desirable. In some embodiments, the Sn concentration may be 0.005M to 1.4M, in further embodiments, 0.02M to 1.2M, and in additional embodiments, 0.1M to 1.0M. Additional ranges of Sn concentrations within the explicit ranges are contemplated and will be recognized by those of skill in the art.
[0046] If deposition is required, [RSnOH(H 2 O)X 2 ] 2 The formation of RSnX can be achieved, for example, by incubating the cells in a chamber isolated from the ambient environment. 3 and H 2 This can be carried out by gas phase reaction with O. The organotin precursor RSnX 3 may be introduced into the chamber by means known to those skilled in the art, such as using a stream of vapor, aerosol and / or direct liquid injection into the vaporization chamber. Water is then introduced into the chamber through a separate inlet, either simultaneously with or after the introduction of the organotin precursor, to promote hydrolysis and deposit [RSnOH(H 2 O)X 2 ] 2 A coating may be formed. In some embodiments, the reaction may be carried out at elevated temperatures relative to ambient. In some embodiments, the gas phase reaction may be carried out multiple times until the desired film thickness is achieved.
[0047] In either deposition method, the substrate can be any material of interest. Exemplary substrates include, but are not limited to, silicon, silica, ceramic materials, polymers, and combinations thereof. In some embodiments, the substrate comprises a flat or substantially flat surface onto which the solution is deposited. In certain embodiments, the substrate is a SiO 2The solution deposition may be performed by any suitable method, including, but not limited to, spin coating, spray coating, dip coating, etc. The deposition solution and substrate may be deposited on the substrate with [(RSn) 12 O 14 (OH) 6 ]X 2 The temperature and time are selected to effectively evaporate the solvent and produce a film comprising [RSnOH(H 2 O)X 2 ] 2 [(RSn) 12 O 14 (OH) 6 ]X 2 In some embodiments, the substrate and deposition solution are subjected to a post-apply bake at a temperature between 60 and 100° C. for a time between 1 and 5 minutes, such as a temperature of 80° C. for a time of 3 minutes. In certain embodiments, [(RSn) 12 O 14 (OH) 6 ]X 2 The membrane has an RMS surface roughness of less than 0.5 nm or less than 0.4 nm. In some examples, the RMS surface roughness is about 0.3 nm. The RMS surface roughness can be determined by methods known in the art, such as atomic force microscopy.
[0048] Halides are undesirable components of tin-based photoresists because they can allow for uncontrolled hydrolysis and / or chemically and structurally non-uniform films. Therefore, it is beneficial to remove the halides from the deposited film. In any of the embodiments described above or below, the halides are represented by the formula [(RSn) 12 O 14 (OH) 6 ]X 2 By contacting the film having the formula (I) with a basic aqueous solution, [(RSn) 12 O 14 (OH) 6 ](OH) 2The conversion of the halide-containing film to a non-halide-containing film may be accomplished in other ways, but it may be desirable to avoid contamination of the material with other metals, so the basic aqueous solution is generally desirably metal-free. Suitable basic aqueous solutions may include, for example, quaternary ammonium compounds (e.g., tetramethylammonium hydroxide, tetrabutylammonium hydroxide, etc.), alkylamine compounds (e.g., diethylamine, ethylamine, dimethylamine, methylamine, etc.), and ammonia. In some embodiments, the basic aqueous solution is an aqueous ammonia solution. The halides may be substantially removed from the film by briefly treating with dilute aqueous ammonia. The ammonia may have a concentration of 5 μM to 100 mM, for example, 5 μM to 50 mM, 5 μM to 10 mM, 5 μM to 1 mM, 5 μM to 100 μM, 5 μM to 50 μM, 5 μM to 10 μM, etc. The short period of time can be, for example, 30 seconds to 30 minutes, such as 30 seconds to 15 minutes, 1 minute to 10 minutes, or 1 minute to 5 minutes. In some examples, the halide is chloride and the film is treated with 10 μM NH 3 (aq) for 3 min. Alternatively, NH 3 (aq) can be puddled onto the film, and the aqueous solution can then be removed by spinning the substrate on a spin coater and drying. After alkaline treatment, [(RSn) 12 O 14 (OH) 6 ](OH) 2 The film may be rinsed with water and dried. Drying may be accomplished by flowing nitrogen over the rinsed film and / or by heating. Removal of the halides may slightly increase the roughness of the film. Thus, in some embodiments, [(RSn) 12 O 14 (OH) 6 ](OH) 2 The film has an RMS surface roughness of less than 1.5 nm, 1 nm or less, or 0.8 nm or less, for example, the RMS surface roughness is in the range of 0.3 nm to 1 nm, 0.3 nm to 0.8 nm, or 0.3 nm to 0.5 nm.
[0049] In some embodiments, [(RSn) 12 O 14 (OH) 6 ](OH) 2 An atomically smooth film (e.g., an RMS surface roughness of less than 0.5 nm) is formed on the substrate, where R is as defined above. [(RSn) 12 O 14 (OH) 6 ](OH) 2 The film is RSnX, where X is a halide. 3 In some examples, the starting material may be formed from a precursor comprising nC 4 H 9 SnCl 3 and the reaction is as follows: nC 4 H 9 SnCl 3 (l) + atmosphere → [nC 4 H 9 SnOH(H 2 O)Cl 2 ] 2 (s) 12[nC 4 H 9 SnOH(H 2 O)Cl 2 ] 2 (s) → [(nC 4 H 9 Sn) 12 O 14 (OH) 6 ]Cl 2 +22HCl(g)+H 2 O(s / g) [(nC 4 H 9 Sn) 12 O 14 (OH) 6 ]Cl 2 (s)+2NH 4 OH(aq) → [(nC 4 H 9 Sn) 12 O 14 (OH) 6 ](OH) 2 (s)+2NH 4 Cl(aq)
[0050] In any of the above or below embodiments, [(RSn) 12 O 14 (OH) 6 ](OH) 2 The film is a photoresist film that can be patterned by irradiating with an electron beam or light having a wavelength in the range of 10 nm to less than 400 nm, such as 10 nm to 350 nm, 10 nm to 300 nm, 50 nm to 300 nm, 100 nm to 300 nm, 150 nm to 300 nm, or 200 nm to 275 nm, to produce an irradiated film. In some embodiments, the irradiation is with light having a wavelength in the range of 10 to 260 nm, such as EUV light having a wavelength of 13.5 nm, or with a wavelength of 125 μC / cm. 2 In certain embodiments, the irradiation includes irradiating with light having a wavelength in the range of 200-260 nm or 250-260 nm. In other embodiments, the irradiation includes irradiating with light having a wavelength in the range of 125 μC / cm 2 More than 200μC / cm 2 More than 300μC / cm 2 or more than 500μC / cm 2 For example, the dose is 1000 μC / cm 2 , 200~1000μC / cm 2 , 300~1000μC / cm 2 or 500~1000μC / cm 2 The irradiation is in the range of [(RSn) 12 O 14 (OH) 6 ](OH) 2At least a portion of the R-Sn bonds (more specifically, C-Sn bonds) in the membrane are cleaved. In some embodiments, sufficient irradiation is applied to cleave up to 5%, up to 10%, up to 25%, up to 50%, up to 70%, up to 90%, or up to 100% of the R-Sn bonds, e.g., 0-100%, 1-100%, 1-90%, 1-70%, or 1-50% of the R-Sn bonds. In other embodiments, sufficient irradiation is applied to cleave 5-100%, 5-90%, 5-70%, 5-50%, 10-100%, 10-90%, 10-70%, or 10-50% of the R-Sn bonds. Cleavage results in detachment of the R group from the membrane.
[0051] In any of the above or below described embodiments, the photoresist film comprises [(RSn) 12 O 14 (OH) 6 ](OH) 2 The film may be patterned by irradiating only selected portions, hi some embodiments, the selected portions are irradiated by "writing" them with the electron beam or by masking certain portions of the film and irradiating the unmasked portions.
[0052] In any of the foregoing embodiments, the method may include post-irradiation treatment of the film. In some embodiments, the post-irradiation treatment comprises exposing the irradiated film to air at ambient temperature (e.g., 20-25° C.) for at least 3 hours, or heating the irradiated film in air at a temperature in the range of 100-200° C. for 2-5 minutes. In certain embodiments, the post-irradiation treatment comprises heating the irradiated film at a temperature in the range of 140-180° C. for 2-4 minutes, such as 140-180° C. for 3 minutes. In other embodiments, the post-irradiation treatment consists of simply exposing the irradiated film to air at ambient temperature for an extended period of time, such as at least 3 hours, at least 5 hours, at least 12 hours, at least 24 hours, at least 2 days, at least 3 days, at least 7 days, or at least 10 days.
[0053] Post-irradiation treatment involves exposing the film to air, which hydrolyzes the irradiated areas of the film and increases the concentration of Sn-OH bonds in the film. Over time, the film becomes more sensitive to atmospheric CO 2 Without wishing to be bound by a particular theory of operation, the adsorbed CO 2 is inserted into the Sn-OH bond to form Sn-HCO 3 Then, the adjacent HCO 3 - Group and OH - The group reacts with H 2 O, thereby forming a simple carbonate (e.g., a carbonate group shared between two adjacent Sn atoms). In some embodiments, the resulting film may have a R q S n O m (OH) x (HCO 3 ) y (CO 3 ) z where R, m, q, x, y and z are as defined above.
[0054] The presence of bicarbonate and carbonate groups in the membrane results in the formation of [(RSn) 12 O 14 (OH) 6 ](OH) 2 10-100% of the R-Sn bonds in the membrane were cleaved [(RSn) 12 O 14 (OH) 6 ](OH) 2 This results in a different dissolution contrast with the membrane. 3 2- The R groups form bridges adjacent to the Sn atoms, inhibiting solubility through bridging. q S n O m (OH) x (HCO 3 ) y (CO 3 ) z is [(RSn) 12 O 14 (OH) 6 ](OH) 2It is less soluble in a particular solvent than [(RSn) 12 O 14 (OH) 6 ](OH) 2 is readily soluble in certain ketones (e.g., 2-heptanone, acetone), whereas R q S n O m (OH) x (HCO 3 ) y (CO 3 ) z is insoluble or poorly soluble. Thus, in some embodiments, the patterned film is 12 O 14 (OH) 6 ](OH) 2 is contacted with a solvent that dissolves [(RSn) 12 O 14 (OH) 6 ](OH) 2 In some embodiments, the unexposed portions of the photoresist layer are removed by contacting the patterned photoresist layer with 2-heptanone for a period of time from a few seconds to a few minutes, such as 15 seconds to 2 minutes, 15 seconds to 1 minute, or 15 to 45 seconds. In a particular example, the patterned photoresist layer was contacted with 2-heptanone for 30 seconds.
[0055] (IV. Component Parts) Components are made by embodiments of the disclosed methods. In some embodiments, the components include a substrate and a film on at least a portion of the substrate, where the film is a [(RSn) 12 O 14 (OH) 6 ](OH) 2 where R is defined as above. The film has (i) a root mean square surface roughness of 0.8 nm or less, (ii) an undetectable level of Cl as detected by X-ray photoelectron spectroscopy. - or (iii) it may have both (i) and (ii).
[0056] In any of the embodiments described above or below, the film may be patterned as disclosed herein to provide a patterned component comprising a substrate and a film on at least a portion of the substrate, the film being R q S n O m (OH) x (HCO 3 ) y (CO3) z where q, x, y, z and m are as defined above.
[0057] In any of the foregoing embodiments, the substrate can be any material of interest. Exemplary substrates include, but are not limited to, silicon, silica, ceramic materials, polymers, and combinations thereof. In some embodiments, the substrate comprises a flat or substantially flat surface over at least a portion of which the film is disposed. In certain embodiments, the substrate is a SiO 2 It is. EXAMPLES
[0058] V. Working Examples material As previously described by Luijten (Recueil des Travaux Chimiques des Pays-Bas 1966,85(9):873-878), (C 4 H 9 Sn) 2 (OH) 2 C l4 (H 2 O) 2 (Sn 2 ) crystals, nC 4 H 9 SnCl 3 (l) (Alfa Aesar, 96%) was placed in a crystallizing dish in a fume hood and Sn 2 The preparation was continued for 3 days until crystallization. 4 H 9 Sn)12O14(OH)8(Sn 12(OH) crystals were prepared as previously described by Eychenne-Baron et al. (. J Organometallic Chem 1998,567(1):137-142).
[0059] Thin Film Coating Sn 2 and Sn 12 Solution deposition precursors of were prepared by dissolving 0.14 g and 0.12 g, respectively, per mL of 2-heptanone (Alfa Aesar, 99%) and filtering through a 0.45 μm PTFE syringe filter. 100 nm of SiO was thermally grown on a p-Si (Silicon Valley Microelectronics, Inc) substrate. 2 acetone, isopropyl alcohol and 18.2 mQ-cm H 2 The precursor solution was added to a 2.54x2.54cm 3D slab, which was then washed with O and annealed at 800°C for 15 min. 2 The sample was then immediately transferred to a preheated hotplate at 80° C. and post-baked for 3 minutes.
[0060] Sn 2 Thin films prepared from were subjected to alkaline treatment. These films were treated with 10 μM NH as-deposited and immediately after PAB at 80 °C. 3 After the alkaline treatment, the membrane was placed in a H 2 Rinse with O 2 Dry with a gun.
[0061] Exposure and Contrast Curves Sn 2 Sn prepared from 12OH films were used for patterning experiments. E-beam exposure was performed using a 30 kV e-beam with a Quanta 3D Dual Beam SEM and NPGS software. Contrast curves were generated by plotting square arrays with linearly increasing doses. Post-exposure aging or bake steps in air were applied as specified in the text. Dose arrays were developed by covering with a few drops of 2-heptanone for 30 s and then annealed in N 2 The samples were dried with a gun. Thickness measurements were collected at each square using a Woolam MX-2000 ellipsometer equipped with a focusing probe. Thickness values were plotted as a function of dose or log dose. Exposure to UV light was performed using a Digital UV Ozone System (Novascan) emitting two wavelengths at λ=254 and 185 nm.
[0062] XPS A Physical Electronics (PHI) 5600 MultiTechnique UHV system was used for X-ray photoelectron spectroscopy (XPS) collection. The base pressure of the main chamber was less than 2x10-10 torr. Monochromatized Al Kα radiation (hν=1486.6 eV, 300 W, 15 kV) was used to acquire Ag 3d, Cl 2p, Sn 3d and Sn MNN Auger spectra. An electron analyzer pass energy of 23.5 eV and an emission angle of 45 degrees were used for the measurements. Peak fits for each spectrum were determined using Casa XPS with Gaussian-Lorentzian line shapes and Shirley backgrounds (Frisch et al., Gaussian 16, Revision A.03, 2016). Atomic concentrations were calculated using published sensitivity factors specific to the XPS system used at 90 degrees between the X-ray source and the electron detector (Perdew et al., Phys. Rev. Lett. 1997, 78(7):1396).
[0063] AFM Atomic force microscopy was performed to measure the RMS roughness values using a Bruker Veeco Innova SPC in tapping mode. Nanoscope Analysis 1.5 was used for background subtraction and noise equalization.
[0064] TPD TPD-MS was performed using a Hiden Analytical TPD Workstation. Membranes were 1x1 cm 2 The samples were cut into 1000 nm samples and inserted into the UHV chamber (approximately 3x10-9 orr) of the instrument. The samples were annealed to 800 °C with a linear heating rate of 30 °C / min. MS were acquired with an electron ionization energy of 70 eV and an emission current of 20 μA. Selected mass-to-charge (m / z) ratios of each sample were observed in MID mode with dwell and stabilization times of 150 ms and 50 ms, respectively.
[0065] SEM Scanning electron microscope images were collected on a Quanta 3D Dual Beam SEM using an electron beam of 30 kV.
[0066] ESI-MS The extracted membrane solution was analyzed on an Agilent 6230 electrospray ionization mass spectrometer. The solution was introduced into the spectrometer at a flow rate of 0.4 mL / min using a syringe pump. N 2 was used at 325 °C and 241 kPa to facilitate vaporization of the solution. 2 (g) was flowed at 8 L / min. The capillary voltage was set at 3500 V, the skimmer at 65 V, and the RF octopole at 750 V. Data was collected in both positive and negative ionization modes with the fragmentation voltage set at 30 V.
[0067] TEM and EELS TEM images were collected on an FEI Titan 80-200 TEM using a 200 keV beam. EELS analysis was performed on a Titan using a Gatan Tridiem energy analyzer with a convergence and collection angle of 10 milliradians. The single tilt cryo-holder Gatan 626 used for TEM and EELS remained stable at -170 °C throughout the experiment. One tilt axis was used to tilt the sample to a Si <110> The zone axis was brought very close and the sample was perpendicular to the beam.
[0068] (Results and Discussion) Sn 2 Atomically smooth Cl-free thin films from: Sn 2 has four Cl ligands (Figure 1). Two Sn atoms share a hydroxyl group. 2 An O molecule is associated with each Sn atom. An n-butyl group is also attached to each Sn atom. Sn 2 The solution precursor was deposited by spin coating and post-apply bake (PAB) at 80 °C to give butyltin dodecamer [(nC 4 H 9 Sn) 12 O 14 (OH) 6 ]Cl 2 (Sn 12 The film is very smooth with a root mean square (RMS) roughness of 0.3 nm. Chloride is an undesirable component of tin-based photoresists because it creates an opportunity for uncontrolled hydrolysis and the generation of chemically and structurally inhomogeneous films that can affect the pattern fidelity at various steps of the patterning process. The chloride salt is converted to the chloride salt of OH - The membrane was converted to a Cl-free membrane by replacing it with OH-stabilized butyltin dodecamer [(nC 4 H 9 Sn) 12 O 14 (OH) 6 ](OH) 2 (Sn 12OH, Figures 2A and 2B) have been reported previously, so - Based on the stronger nucleophilic properties of OH - Cl - was assumed to be exchanged for
[0069] Therefore, Sn 12 Immediately after deposition of the Cl film, 10 M NH 3 (aq) for 3 min followed by soft PAB at 80 °C. The top XPS (X-ray photoelectron spectroscopy) spectrum in Figure 3 shows strong Cl 2p1 / 2 and 2p3 / 2 signals in the film deposited before base immersion and after PAB. The bottom spectrum shows strong Cl 2p1 / 2 and 2p3 / 2 signals in the film deposited before base immersion and after PAB. 3 The results show that the Cl signal becomes integrated into the background when immersed in NH 3 (aq) for 3 min to remove Cl from the film. - is removed, and the 12-mer OH - This is interpreted to mean that salt was produced.
[0070] NH 3 After the (aq) bath, surface images of the film were collected by atomic force microscopy (AFM) (Figure 4A and Figure 4B). The RMS roughness of the resulting film increased slightly from 0.32 nm to 0.45 nm, indicating an atomically smooth surface. 2 The smooth morphology of the film prepared from Sn was not significantly deteriorated. 2 Sn from precursors 12 When Sn is deposited, 12 This produces a much smoother film than deposition directly from the precursor. Equations 1 and 2 are 2 This paper summarizes the chemical reactions of n-butyltin oxohydroxo from solid crystals to atomically smooth, Cl-free, patternable thin films.
[0071] Deposition and PAB: 6[(nC 4 H 9 Sn)Cl 2 (OH)(H 2 O)]2 →[(nC 4 H 9 Sn) 12 O 14 (OH) 6 ]Cl 2 (s) + 22HCl(g) + H 2 O(s / g) (Equation 1)
[0072] Base Soak: [(nC 4 H 9 Sn) 12 O 14 (OH) 6 ]Cl 2 (s)+2NH 4 OH(aq) → [(nC 4 H 9 Sn) 12 O 14 (OH) 8 ](s)+2NH 4 Cl(aq) (Eq. 2)
[0073] Sn 2 The film coated from the Sn on the wafer after PAB and base immersion 12 To confirm that OH speciation occurs, Sn 12 Bulk crystals of SnOH were prepared and deposited from a 2-heptanone solution. 2 and Sn 12 The deposition and process parameters of the OH solution precursor were: Sn 2 Film (Sn 12 Cl) to NH 3 The only difference was that the mixture was ion-exchanged in (aq) for 3 min.
[0074] Table 1 shows the chemical composition and Sn determined from the XPS data. 12 The calculated composition based on the formula of Sn OH is summarized below. 2 The atomic concentrations of Sn, O, C and Cl in the films fabricated from 12 The match was within 3% with films processed from OH and within 2% with the composition predicted from the molecular formula.
[0075] [Table 1]
[0076] Figures 5A and 5B show temperature programmed desorption (TPD) spectra collected for both membranes. The desorption mass, peak signal temperature, and relative peak intensities were indistinguishable between the two membranes. The membranes were extracted by immersion and dissolution in methanol to create a solution for evaluating speciation on the wafer. Electrospray ionization mass spectrometry (ESI-MS) of the extracted membrane solutions was identical (Figure 6) and revealed two major peaks centered at mass-to-charge ratios (m / z) of approximately 1250 and 2500. These peaks correspond to the parent Sn 12 The observed complex lines correspond to the +2 and +1 ions of the OH dodecamer. The -OH and -OCH 3 This is the result of ligand exchange.
[0077] The ESI-MS spectra of the two samples showed that -OH was replaced by -OCH 3 They are distinguished by varying degrees of peak splitting due to partial exchange with the ligand. This exchange can only occur during the dissolution process in methanol, since the source of methoxo ligand is introduced first and only to the system. Thus, the splitting of the characteristic peaks does not represent differences in speciation on the wafer.
[0078] XPS, TPD, and ESI-M show that the Sn on the wafer is stable regardless of the identity of the solution precursor. 12 This provides complementary evidence for OH speciation. 2 From Sn 12 Assists in the conversion to OH.
[0079] Organotin photoresists are typically applied, irradiated, and then heated in lithography processes. These materials must maintain low surface roughness to produce high-resolution patterns. NH 3An additional 3 min bake was performed after (aq) treatment to evaluate the roughness behavior at increasing temperatures. Figure 7 shows that films baked at 140-180 °C maintain an RMS roughness of about 0.75 nm despite the initial surface roughness. This data suggests that films subjected to typical PAB and PEB processing temperatures continue to exhibit excellent roughness below 0.75 nm, a prerequisite for high resolution photoresist materials. Although the speciation on the wafer is identical, all radiation experiments were performed with a focus on Sn 2 The study was carried out on Cl-free films prepared from Sn 2 The process is Sn 12 It produced a smoother surface (RMS = 0.45 nm) than the direct deposition of OH (RMS = 1.32 nm). 12 When the film directly processed from OH was baked, the surface morphology rapidly roughened to 4.43 nm by 140 °C.
[0080] Patterning Chemistry Non-exposed membrane to establish baseline: Run TPD-MS to measure Sn 2 The thermally induced desorption spectrum from a Cl-free thin film prepared from was analyzed. The spectrum shown in Figure 8 shows the H 2 O, CO 2 , revealing three major leaving signals from the n-butyl ligand.
[0081] Figure 8 shows three low intensity signals at temperatures below 200°C. The water peak at 75°C corresponds to the H 2 This peak is due to the desorption of H. This peak became larger after 11 days of atmospheric aging (Fig. 9A). This is because the film absorbed H 2 This suggests that O(g) is slowly and continuously adsorbed. 2 The peaks are from the metal oxide surface and CO 2 (g) Weakly adsorbed CO 2 These two CO 2The relative intensities of the desorption peaks were found to change erratically over time in air (Figure 9B). This behavior is consistent with the weakly adsorbed CO on the metal oxide surface. 2 By adopting a soft bake in air at 140 °C for 3 min, the three low-temperature H 2 O and CO 2 The desorption peaks were significantly reduced (Figure 10). These peaks below 200°C are due to weakly bonded H 2 O and CO 2 It was concluded that this represented desorption of the adsorbent.
[0082] The most intense desorption event from the TPD spectrum in Figure 8 occurred at 400 °C and revealed peaks related to various organic fragments. Thermally induced Sn-C bond cleavage accompanied by H removal or extraction resulted in the formation of 1-butene (C), respectively. 4 H 8 ) (Figure 11) or n-butane (C 4 H 10 ) (Figure 12). Based on the known fragmentation patterns of both products, it was expected that the propyl fragment would be the most intense signal upon ionization dissociation. Figure 13 shows the propyl chain [m / z=41 (C 3 H 5 ), m / z=43(C 3 H 7 )] are shown to represent the 1-butene and n-butane products, respectively.
[0083] 1-Butene (C 4 H 8 ) (Figure 10) and n-butane (C 4 H 10) (Figure 12) have similar patterns in the ionizer, making it difficult to determine the relative amounts without standardization of the mass spectrometer. However, the expected intensity at m / z=43 is 100% for n-butane and essentially 0% for 1-butene. The experimental spectra showed a substantial m / z=43 peak, indicating well that Sn-butyl pyrolysis of these films resulted in the production of both n-butane and 1-butene decomposition products entering the mass spectrometer. Here, m / z=41 and onwards are used to represent the relative butyl concentrations in the films after various treatments, since these were the most intense peaks.
[0084] At 400 °C, m / z = 18 and 44 also peaked. At this temperature, m / z = 44 is CO 2 or C 3 H 8 (butane product fragment). However, M / z=18 is due to C 4 H 8 or C 4 H 10 Since the TPD experiment did not induce the pyrolysis of Sn-butyl and produce H as a by-product, 2 Finally, the weak CO detected at 600 °C was assigned to water. 2 The peaks are indicated by asterisks in FIG.
[0085] Exposed film 1x1cm 2 The film was irradiated with an electron beam and immediately subjected to TPD analysis. The exposed area corresponds to the dimensions of the sample required for TPD analysis. Figure 14 shows the results of the electron beam irradiation at 0 (black), 300 (blue), and 1000 (red) μC / cm 2Figure 14 shows the signal associated with n-butyl desorption (m / z=41) from a sample exposed to 1000 dl / s. The intensity of the desorption signal decreased with increasing dose, suggesting a decrease in n-butyl content with increasing dose (Figure 15). The curves in Figure 14 show three indicators of zero-order desorption kinetics: aligned leading edges, separated trailing edges, and offset peak temperatures. TPD measurements reveal that electron beam irradiation breaks Sn-C bonds and causes outgassing of n-butyl ligands, thereby reducing the organic ligand concentration in the film.
[0086] The TPD data in Figure 14 shows the change in C 3 H 5 The signal reduction is summarized. The inset shows the R 2 = 0.98. The film thickness from spectroscopic ellipsometry also showed an exponential decrease as a function of dose (Figure 16) (R 2 = 0.97). As a result, these data show that the probability of Sn-C bond cleavage is simply proportional to the concentration of Sn-C bonds in the film, i.e., the concentration of butyl groups in the film.
[0087] The removal of the butyl ligands and the associated changes in film thickness and density demonstrated that exposed and unexposed areas of the film could be imaged and characterized by electron microscopy (EM). 2 Two Sn were prepared using a 30 kV electron beam at a dose of 12 Fine lines (~25 nm) were written on the OH films with a 100 nm pitch. One film was developed for 30 s in 2-heptanone immediately after a post-exposure bake (PEB) at 140 °C for 3 min to confirm via scanning electron microscopy (SEM), which indeed revealed 25 nm lines spaced 75 nm apart (Figure 17).
[0088] The second film was not developed. Because the patterned film is highly sensitive to heat, cryo-focused ion beam milling was used to extract electron-transparent lamellae for EM analysis. Prior to milling, a layer of chromium was deposited, followed by protective coatings of C and Pt, all via evaporation methods. Additional beam damage was prevented by collecting scanning transmission electron microscopy (STEM) images and carbon electron energy loss spectroscopy (EELS) data at ultra-low temperature (77 K).
[0089] Figure 18 shows a reverse contrast cross-sectional cryo-STEM image of an exposed and undeveloped sample. From bottom to top, each layer is 2 Substrate (light gray), exposed Sn 12 OH (black), corresponding to the protective chrome layer (dark grey). The periodic dark areas spaced approximately 75 nm apart represent exposed areas of the resist. These match the line spacing observed in the fully developed pattern (Figure 17). Clearly, cryo-STEM in combination with high atomic number contrast enables a unique approach that allows direct imaging of the normally invisible latent image in inorganic photoresists.
[0090] FIG. 19 shows a Sn ion beam parallel to the substrate, performed at 10 nm resolution. 12 Carbon EELS line scans through the OH film are shown. The data showed three distinct drops in carbon resulting from three areas of exposure across the line scan. The lowest carbon count in each line corresponds to a 50% loss of carbon, which corresponds to 50% of the butyl ligands. Similar results were obtained with the carbon EELS point scan. These data provide further evidence that irradiation breaks Sn-C bonds, which leads to desorption of organic species from the film.
[0091] Considering the difficulties of FIB sample preparation and cryo-EM measurements, the ~50% loss of butyl ligands is comparable to the ~40% loss observed in TPD. The 10 percentage point difference can be attributed to statistical variations in film deposition and processing, as well as potential carbon losses during cryo-FIB milling and cryo-STEM analysis.
[0092] Retardation after atmospheric exposure: Following the procedures detailed in the experimental section, electron beam exposure was performed in the vacuum chamber of the SEM to generate five controlled dose arrays. After imaging, the sample was removed from the vacuum environment and aged in air before being developed for 30 seconds in 2-heptanone. One array was left undeveloped. Figure 20 shows the film thickness as a function of dose for arrays aged 0.25, 3, 24 and 144 hours. The undeveloped array serves to identify the delay time required to maintain 100% of the pre-development film thickness.
[0093] All exposed pads from samples subjected to a 0.25 hour delay simply dissolved in 2-heptanone, with no difference in dissolution rate between exposed and unexposed areas of the film. After 3 hours in air, the high dose pads (200 μC / cm 2 A decrease in dissolution rate was observed at 125 μC / cm after a 24-hour delay. 2 Dissolution begins around 200μC / cm 2 The contrast saturates near 0.1, where the pad thickness is equal to that of the latent image control. Continuing aging beyond 24 hours resulted in less change in sensitivity. The highest contrast achieved after 24 hours of aging in air was 5.1. It is clear that the delay time between exposure and development plays a large role in the difference in dissolution rates.
[0094] To determine whether the slow aging changes were due to exposure alone or to a reaction with atmosphere, a direct comparison was made between arrays aged in vacuum and air for 2 hours each. Figure 21 shows that only the air-retarded samples produced a clear contrast between exposed and unexposed areas upon development in acetone. These observations suggest that the effects of one or more atmospheric components [CO 2 (g), H 2 O(g), O 2 It was concluded that absorption of (g)] was necessary. The array in Figure 21 was developed with acetone only. Acetone was used as the developer in this experiment because a shorter delay time (>24 h) was needed to observe the change in solubility. 2-heptanone was used for all other development steps reported because it gives higher contrast.
[0095] Two 1x1cm 2 The sample was heated to 1000μC / cm 2 The films were exposed to 1000 s of electron beam radiation. After exposure, one sample was immediately transferred to the ultra-high vacuum (UHV) chamber of the TPD instrument, while the other sample was aged in air for 10 days. The transfer from SEM to TPD took about 15 min. An arbitrarily high exposure dose combined with a long delay time in air was chosen to maximize the reaction products on the film and thereby maximize the desorption signal in the TPD-MS.
[0096] 22A-22C show the n-butyl, H 2 O and CO 2 The desorption signals are shown. All three species are at 1000 μC / cm 2 It shows that there is an overall decrease in desorption after exposure to .
[0097] 23A to 23C are 1000 μC / cm 2 The results are shown in Table 1. n-Butyl (23A), H 2O (23B) and CO 2 The desorption curve of (23C) is shown. 23B The 10-day delay in the atmosphere is due to the higher intensity H 2 The low-temperature signal of water desorption in the structure (Figure 9A) reveals that the H 2 The temperature shifted from 75 to 90 °C due to the increase in O concentration. 2 A higher signal for the desorption of O is expected, as these membranes absorb H from the atmosphere. 2 It was shown that the oxidized β-O adsorbent was highly effective against the oxidized β-O adsorbent (Figure 9A). 2 O desorption indicated that the aged membranes were more extensively hydroxylated than the non-aged membranes. As a result, the hydrophilic aged membranes absorbed more water. This is because the H 2 This is evident from the higher O elimination signal.
[0098] figure 23C is the CO 2 Identify the signal. The exposed sample aged in air for 10 days shows a significantly higher CO signal compared to the unaged film. 2 Desorption signals were observed. The area under the exposed curve is about four times that of the unaged curve. These signals are due to weakly bound CO 2 Desorption only occurs at temperatures above 200°C, rather than at the adsorbate (Figure 9B). 23C As a signal for HCO 3 - and CO 3 2- Related to.
[0099] Finally, Fig. 23A The exposure curves for show that the onset of butyl elimination shifted from 300 °C to 175 °C and the peak signal shifted from 400 °C to 350 °C after a 10-day delay in air. The same trend was observed for m / z=43 (C 3 H 7 ), 56(C 4 H 8) and 58(C 4 H 10 ) was also observed for other organic fragments (Figure 24). 23A The areas under the curves for n-butyl elimination and high temperature H2O from 400 °C to 350 °C agree with each other to within 5%, indicating that there is virtually no change in the concentration of remaining ligands after aging. These spectra reveal that the outgassing of organics is limited only to the exposure process, and that the chemical environment of the remaining butyl ligands has changed after aging in air. 2 Shifts in both peak signals for O elimination (Figure 23B ) goes on to demonstrate that high temperature water elimination is a by-product associated with n-butyl decomposition.
[0100] Although weaker intensities were observed, the same trend was observed at 300 μC / cm 2 and 500 μC / cm 2 followed by exposure to air for 1 or 6 days delay (Figures 25A-25C, 26A-26C).
[0101] 27A to 27C show the Sn 12 We show that the n-butyl groups can be removed by heating the film in air (27A). These n-butyl-depleted films were then subjected to H 2 O(27B) and CO 2 It absorbs (27C) to produce hydroxides, bicarbonates, and carbonates.
[0102] The TPD experiment was repeated with immediate and air-delayed samples exposed to ultraviolet (UV) light (λ = 254 nm). Samples were exposed for 10 min. One sample was immediately brought to the UHVTPD chamber, while the other sample was aged in air for 6 days. Figure 28 shows the butyl desorption from the exposed sample compared to the signal from the unexposed sample. The data shows that the m / z = 41 peak is completely removed. This means that the exposure dose was sufficient to break all Sn-C bonds and evolve the ligand products. No other butyl-related desorbed masses were detected, ensuring complete removal and not degradation fragments trapped in the film.
[0103] Figure 29 shows the H 2 The difference in the O desorption spectrum is negligible. 2 The desorption is shown in Figure 30. Again, after aging in air, a significantly higher desorption signal is observed. m / z=44 (CO 2 + ) and 28(CO + ) shows that m / z=44 is actually CO 2 This provides further confidence that the
[0104] Carbon dioxide is shown to smoothly insert into the Sn-O bonds of tin alkoxides and tin hydroxides on metal oxide surfaces. x O y There have been many reports on the incorporation of carbonates into the core. For example, di-n-butyltin oxide was used to efficiently incorporate CO 2 It is also said to be a scavenger.
[0105] While not wishing to be bound by any particular theory of operation, the chemical reactions in Figure 32 contribute to the differential dissolution of n-butyltin oxide hydroxide. Upon electron beam or UV exposure, the Sn-C bonds are broken, promoting the elimination of the butyl ligands as butane or butene. When the sample is introduced into air, the Sn sites in the exposed areas hydrolyze, forming Sn-OH. -Over time, the membrane absorbs more CO 2 and inserts into the Sn-OH bond to form a bicarbonate. Next, the adjacent bicarbonate reacts to form H 2 O and form simple carbonates. The formation of Sn carbonates is 3 2- Condensation through the bridge can inhibit dissolution. Terminal carbonate ligand HCO bound to Sn 3 - The formation of 2-(2,4-dichlorophenyl)-2,4-difluorophenylcarbonate may also affect solubility due to the significantly different polarity compared to the n-butyl ligand. Either carbonate species may result in a different solubility contrast.
[0106] The gradual change in dissolution rate (Figure 20) is due to the gradual CO 2 This was confirmed to be a direct result of adsorption and therefore the gradual bicarbonate and carbonate formation. Since a decrease in the n-butyl decomposition temperature was observed, it was hypothesized that the formation of carbonate species weakened the Sn-C bond (Figure 23C).
[0107] Figure 33 shows the Sn exposed to the electron beam. 12 To achieve dissolution contrast in the membrane, 2 O and CO 2 We demonstrate that both are necessary. Three different dose arrays were measured in air (baseline), in a desiccator (H 2 O-depleted environment) and wet glove box (CO 2 The films were exposed in a 24-h delayed atmosphere (starved environment) and developed in 2-heptanone for 30 s. The radiation-exposed films were then degassed in CO 2 When aged in a humid environment (wet glove box) without any solvent, they showed no dissolution contrast.
[0108] O 2 M / z = 32, corresponding to , was not detected above the baseline in any of the TPD experiments. 2(g) When delayed for 24 hours in the ambient environment, no patterns were observed upon development (recording the loss of n-butyl (34A) and water (34B), Figures 34A-34B). These data indicate that, at least alone, O 2 (g) suggests that the radiation-evoked response is not completed, so its involvement was excluded.
[0109] Post Exposure Bake Figure 35 shows thickness measurements of dose arrays exposed to no PEB, 100° C. PEB, 140° C. PEB, and 180° C. PEB for 3 minutes. All samples were then immediately developed in 2-heptanone for 30 seconds so that there was no additional delay time apart from the 3 minute PEB.
[0110] The unbaked dose arrays, when developed immediately after removal from vacuum, revealed no dissolution contrast. The 100 °C baked sample had a dissolution contrast of 300 μC / cm 2 The dissolution rate decreased at nearby doses. After 140°C and 180°C, the pads reached 260 μC / cm 2 and 200 μC / cm 2 These data show that using PEB at T ≥ 140 °C, the pre-development thickness is 300 μC / cm 2 Figure 36 shows that exposure doses less than 100 nm provide sufficient energy to produce insoluble products and avoid lag times. 12 This indicates detachment from the membrane.
[0111] The electron beam exposure followed by TPD was repeated, this time on a 1x1cm 2 A PEB step was added to the large exposed area of 1000 μC / cm. 2 Only two of them were exposed at 1000 s and immediately subjected to PEB at 140 °C and 180 °C for 3 min. They were then quickly placed in the UHV chamber of the TPD to minimize exposure to air. The desorption spectrum after PEB was observed to be nearly identical to that after a long delay in air.
[0112] Figure 37 shows the CO 2 The signal increases significantly with increasing PEB temperature, suggesting an increase in the concentration of carbonate species. Also, increasing the PEB temperature shifts the n-butyl desorption to a lower peak temperature, indicating that H 2 It also shows an increase in O-elimination (Figures 34A, 38A, and 38B). After 3 min of PEB at 320° C., 80% of the butyl ligands were lost. Both of these trends are consistent with the results of samples aged at room temperature in air for extended periods.
[0113] Figures 35 and 37 suggest that the exposed samples do not result in differential dissolution when developed immediately after exposure in vacuum, since the carbonate concentrations are relatively low. However, when higher concentrations of carbonate species are observed, dissolution is effectively suppressed. The PEB process is simply a reaction of CO with hydrolyzed Sn. 2 (g) It was concluded that it provides enough energy to activate the reaction, increasing the rate of reaction.
[0114] -OH bonded to Sn - An evaluation was performed to determine whether Sn is an active site for carbonate formation. To do this, both unexposed and exposed samples were heated to 180 °C in air and the desorption spectra were compared before and after heating. Baking the unexposed sample essentially freed the intact Sn 12 Baking the exposed sample represents baking of the butyl-deficient Sn atoms that were hydrolyzed upon introduction into the atmosphere.
[0115] 39 and 40A-40B show three species (n-butyl, H 2 O, CO 2 ) shows that all desorption spectra changed dramatically when the exposed sample was baked in air. As mentioned above, the exposed film baked at 180 °C showed no significant difference in the desorption spectra when exposed to CO. 2This indicates an increase in the desorption of Sn-OH groups, suggesting an increase in carbonate groups in the film. When the unexposed sample was baked, the desorption spectrum hardly changed before and after heating. Therefore, it is considered that Sn-OH - The part is CO 2 It was concluded that (g) absorbs and forms bicarbonate and carbonate.
[0116] HCO 3 - and CO 3 2- It was hypothesized that both CO and CO are formed in the films during aging in air or baking at temperatures up to 180 °C (Figures 23B, 37, and 41A-41C). 2 The peak is H in that temperature range. 2 O signals were also observed, which was attributed to the decomposition of Sn bicarbonate. 2 No O peak was detected, so CO 2 The peak probably represents the decomposition of Sn carbonate.
[0117] Thermogravimetric analysis-mass spectrometry was performed to determine the bulk Sn 12 The TGA-MS was performed in a simulating partial exposure to OH powder. 2 In Sn 12 Run in OH to establish a baseline (Figure 42A) and Sn 12 The OH was baked in air to decompose some of the butyl ligands, thereby mimicking light exposure (Figure 42B). The same trend was observed for the bulk powder.
[0118] Patternability – Proof of Concept: Based on all the aforementioned observations, Sn 12 OH is 400μC / cm 2 The Sn was lithographically patterned with PEB at 140 °C and developed in 2-heptanone for 30 seconds. Figure 43 shows SEM images of 10 nm lines with 60 nm pitch in the horizontal direction and 14 nm lines with 60 nm pitch in the vertical direction. The difference in line width between the horizontal and vertical lines is due to the difference in beam step size in the two directions. Figure 44 shows the Sn 2Deposition, N.H. 3 (aq) Sn by immersion 12 13A-13C are SEM images of line and space and dot patterns produced by the process of conversion to OH, e-beam exposure, post-exposure bake at 180° C., and development with 2-heptanone.
[0119] (Conclusion) Atomically smooth Sn without Cl 12 A method was developed to produce OH films, which represent a model system to elucidate the chemical processes that contribute to their high-resolution patterning capabilities. TPD-MS was used to analyze the chemical changes in the films after exposure to radiation, aging in air, and baking. Cryo-STEM and cryo-EELS measurements confirmed the TPD results. The spectra showed that the radiation cleaved Sn-C bonds and induced the desorption of butane and butene. When introduced into air, the exposed films evolved into H 2 O(g) and CO 2 (g) and form hydroxides, bicarbonates, and carbonates. In films aged at room temperature, limited evidence of extensive condensation was found. Here, OH - , HCO 3 - and CO 3 2- The exchange of n-butyl ligands for H may be sufficient to induce a dissolution rate contrast between exposed and unexposed areas of the film. 2 O(g) and CO 2 (g) accelerates absorption and produces a dissolution contrast similar to that of aging. The amount of additional crosslinking that may occur with baking requires further study.
[0120] In view of the many possible embodiments to which the principles of the disclosed invention may be applied, it is to be recognized that the illustrated embodiments are merely preferred examples of the invention and should not be construed as limiting the scope of the invention. Rather, the scope of the invention is defined by the following claims. We therefore claim as our invention all that comes within the scope and spirit of these claims.
Claims
1. R q SnO m (OH) x (HCO 3 ) y (CO 3 ) z wherein: R is (i) C 1 ~C 10 or (ii) a heteroaliphatic, heteroaryl or heteroaryl-aliphatic containing 1 to 10 carbon atoms and one or more heteroatoms, where R is bonded to Sn through a C-Sn bond; 0.1≦q<1, 0<x≦4, 0<y≦4, 0<z≦2, m=2−q / 2−x / 2−y / 2−z, and (q / 2+x / 2+y / 2+z)≦2, The composition.
2. R is C 1 ~C 10 The composition of claim 1 which is aliphatic.
3. R is C 1 ~C 5 The composition of claim 1 wherein the alkyl group is an alkyl group.
4. The composition of claim 1 , wherein R is n-butyl.
5. 0.1≦q<1, 0<x≦3.9, 0<y≦3.9 and 0<z≦1.95, The composition according to any one of claims 1 to 4, wherein
6. (i) 0<x≦3, or (ii) 0<y≦3, or (iii) 0<z≦1.5, or (iv) any combination of (i), (ii), and (iii); 6. The composition according to any one of claims 1 to 5.
7. R q SnO m (OH) x (HCO 3 ) y (CO 3 ) z wherein: R is (i) C 1 ~C 10 or (ii) a heteroaliphatic, heteroaryl, or heteroaryl-aliphatic group containing 1 to 10 carbon atoms and one or more heteroatoms; 0.1≦q<1, 0<x≦3.9, 0<y≦3.9, 0<z≦1.95, m=2−q / 2−x / 2−y / 2−z, and (q / 2+x / 2+y / 2+z)≦2 The composition.
8. A substrate; A film on at least a portion of the substrate, the film comprising the composition of any one of claims 1 to 7; and A component comprising:
9. The component of claim 8 , wherein the film is patterned on the substrate.
10. (i) the membrane has an average thickness in the range of 2 to 1000 nm; or (ii) the membrane has a root mean square surface roughness of less than 1.5 nm; or (iii) both (i) and (ii); Component according to claim 8 or claim 9.
11. RSnX 3 is exposed to the atmosphere, thereby 2 O) X 2 ] 2 where X is a halogen and R is selected from the group consisting of: (i) C 1 ~C 10 or (ii) a heteroaliphatic, heteroaryl, or heteroaryl-aliphatic group containing 1 to 10 carbon atoms and one or more heteroatoms; The above [RSnOH(H 2 O) X 2 ] 2 preparing a solution comprising: depositing the solution onto a substrate; The deposited solution and the substrate are heated to form [(RSn) 12 O 14 (OH) 6 ]X 2 forming a film on a substrate comprising: [(RSn) 12 O 14 (OH) 6 ]X 2 The film comprising the compound is contacted with an aqueous ammonia solution to form a film of [(RSn) 12 O 14 (OH) 6 ]X 2 and producing a membrane comprising: [(RSn) 12 O 14 (OH) 6 ](OH) 2 irradiating at least a portion of the film with an electron beam or light having a wavelength in the range of 10 nm to less than 400 nm to produce an irradiated film; Including, (i) exposing the irradiated film to air at ambient temperature for at least 3 hours; or (ii) heating the irradiated film in air at a temperature in the range of 100-200° C. for 2-5 minutes; Further comprising: This allows the irradiated portion of the film to absorb atmospheric CO 2 Adsorb R q SnO m (OH) x (HCO 3 ) y (CO 3 ) z where 0.1≦q<1, 0<x≦4, 0<y≦4, 0<z≦2, m=2−q / 2−x / 2−y / 2−z and (q / 2+x / 2+y / 2+z)≦2.
12. R is C 1 ~C 10 The method of claim 11 , wherein the organic solvent is aliphatic.
13. R is C 1 ~C 5 The method of claim 11 , wherein the alkyl group is an alkyl group.
14. The method of claim 11, wherein R is n-butyl.
15. The deposited solution and the substrate are heated to deposit [(RSn) 12 O 14 (OH) 6 ]X 2 15. The method of any one of claims 11 to 14, wherein producing a film comprising comprises heating at a temperature in the range of 60-100°C for 1-5 minutes.
16. The irradiation is Irradiating with light having a wavelength in the range of 10 to 260 nm; or 125 μC / cm 2 Irradiating the electron beam with a dose of at least one of the above. The method of claim 11 , comprising:
17. The irradiation is 125 to 1000 μC / cm 2 The method of claim 16, comprising irradiating the electron beam with a dose of
18. The irradiation is carried out by the reaction of [(RSn) 12 O 14 (OH) 6 ](OH) 2 The method of any one of claims 11 to 17, wherein 10-100% of the R-Sn bonds of the irradiated portion of the film are broken.
19. The method of claim 11, wherein 0.1≦q<1, 0<x≦3.9, 0<y≦3.9 and 0<z≦1.
95.
20. (i) exposing the irradiated film to air at ambient temperature for 1 to 10 days; or (ii) the irradiated film is heated at a temperature in the range of 140-180° C. for 3 minutes; 20. The method of claim 11 or 19.
21. [(RSn) 12 O 14 (OH) 6 ](OH) 2 a portion of the film comprising the first and second electrodes is irradiated to form a patterned film; The patterned film is then treated with [(RSn) 12 O 14 (OH) 6 ](OH) 2 wherein the irradiated portion of the film is contacted with a solvent in which [(RSn) 12 O 14 (OH) 6 ](OH) 2 21. The method of any one of claims 11-15 and 17-20, wherein the irradiated portion of the patterned film is rendered less soluble for a time effective to dissolve the irradiated portion of the patterned film.
22. A substrate; a film on at least a portion of the substrate, the film comprising: R q SnO m (OH) x (HCO 3 ) y (CO 3 ) z wherein 0.1≦q<1, 0<x≦4, 0<y≦4, 0<z≦2, m=2−q / 2−x / 2−y / 2−z, and (q / 2+x / 2+y / 2+z)≦2. A component manufactured by the method according to any one of claims 11 to 18, 20 and 21.
23. The component of claim 22, wherein 0.1≦q<1, 0<x≦3.9, 0<y≦3.9 and 0<z≦1.95.
Citation Information
Patent Citations
High-resolution patterning compositions and corresponding methods based on organometallic solutions
JP2018502173A